The Effect of Training on Employee Performance by Mediating Organizational Commitment and Motivation at the Labuhanbatu Youth and Sports Culture and Tourism Service - Mahroni Permata Indah Siagian; Zulkifli Musanip Siregar; Bhakti Helvi Rambe (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
The study aims to analyze the effect of training on employee performance with organizational commitment and motivation as mediating variables. This research was conducted at the Labuhanbatu Youth and Sports Culture and Tourism Office. This study uses a quantitative method with path analysis (Path Analysis). This study uses an analytical tool in the form of IBM SPSS 25 Software to facilitate the analysis process. On the results of the t-test on training (X) on organizational commitment (Z1) it has a tcount (3.84) > ttable (1.66) which means Ha is accepted and Ho is rejected, with a significance value smaller than the probability value or 0.000 <0 .05 it can be concluded that training (X) has a positive and significant influence on organizational commitment (Z1). The t-test on training (X) on motivation (Z2) has a tcount (4.18) > ttable (1.66) which means that Ha is accepted and Ho is rejected, with a significance value smaller than the probability value or 0.000 <0.05, so it can be concluded that training (X) has a positive and significant effect on motivation (Z2). The t-test on training (X) on employee performance (Y) has a tcount (5.54) > ttable (1.66) which means Ha is accepted and Ho is rejected, with a significance value smaller than the probability value or 0.000 <0.05 it can be concluded that training (X) has a positive and significant influence on employee performance (Y). The t-test on organizational commitment (Z1) to employee performance (Y) has a tcount (7.99) > ttable (1.66) which means that Ha is accepted and Ho is rejected, with a significance value smaller than the probability value or 0.000 <0. 05 it can be concluded that organizational commitment (Z1) has a positive and significant influence on employee performance (Y). The t-test on motivation (Z2) on employee performance (Y) has a tcount (11.20) > ttable (1.66) which means Ha is accepted and Ho is rejected, with a significance value smaller than the probability value or 0.000 <0.05 it can be concluded that motivation (Z2) has a positive and significant influence on employee performance (Y).